Global Survey on Pancreatic Surgery During the COVID-19 Pandemic. Issue 2 (August 2020) - Oba, Atsushi; Stoop, Thomas F.; Löhr, Matthias; Hackert, Thilo; Zyromski, Nicholas; Nealon, William H.; Unno, Michiaki; Schulick, Richard D.; Al-Musawi, Mohammed H.; Wu, Wenming; Zhao, Yupei; Satoi, Sohei; et al.
Abstract : Objective: The aim of this study was to clarify the role of pancreatic surgery during the COVID-19 pandemic to optimize patients' and clinicians' safety and safeguard health care capacity. Summary Background Data: The COVID-19 pandemic heavily impacts health care systems worldwide. Cancer patients appear to have an increased risk for adverse events when infected by COVID-19, but the inability to receive oncological care seems may be an even larger threat, particularly in case of pancreatic cancer. Methods: An online survey was submitted to all members of seven international pancreatic associations and study groups, investigating the impact of the COVID-19 pandemic on pancreatic surgery using 21 statements (April, 2020). Consensus was defined as >80% agreement among respondents and moderate agreement as 60% to 80% agreement. Results: A total of 337 respondents from 267 centers and 37 countries spanning 5 continents completed the survey. Most respondents were surgeons ( n = 302, 89.6%) and working in an academic center ( n = 286, 84.9%). The majority of centers ( n = 166, 62.2%) performed less pancreatic surgery because of the COVID-19 pandemic, reducing the weekly pancreatic resection rate from 3 [interquartile range (IQR) 2–5] to 1 (IQR 0–2) ( P < 0.001). Most centers screened for COVID-19 before pancreatic surgery ( n = 233, 87.3%). Consensus was reached on 13 statements and 5 statements achieved moderate agreement. Conclusions: This global survey elucidates the role of pancreatic surgery during the COVID-19 pandemic, regarding patient selection for the surgical and oncological treatment of pancreatic diseases to support clinical decision-making and creating a starting point for further discussion. Abstract : Supplemental Digital Content is available in the text